2014
DOI: 10.1088/0022-3727/47/46/465103
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen vacancy andEC− 1 eV electron trap in ZnO

Abstract: Fourier transform deep level transient spectroscopy has been performed between 80 K and 550 K in five n−type ZnO samples grown by different techniques. The capture cross section and ionization energy of four electron traps have been deduced from Arrhenius diagrams. A trap 1 eV below the conduction band edge is systematically observed in the five samples with a large apparent capture cross section for electrons (1.6 ± 0.4 × 10 −13 cm 2 ) indicating a donor character. The assignment of this deep level to the oxy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…Deep level transient spectroscopy (DLTS) has been used extensively to study defects in ZnO. There are several levels that are observed in many samples, particulary under suitable conditions for oxygen vacancy formation, within the ranges 0.27-0.31 eV and 0.60-0.67 eV [93][94][95][155][156][157][158][159][160][161][162]. Our computed (2 + /0) using BB1k agrees well with the former DLTS signal and is a transition that we would expect to contribute significantly in the samples used experimentally.…”
Section: Znomentioning
confidence: 99%
See 1 more Smart Citation
“…Deep level transient spectroscopy (DLTS) has been used extensively to study defects in ZnO. There are several levels that are observed in many samples, particulary under suitable conditions for oxygen vacancy formation, within the ranges 0.27-0.31 eV and 0.60-0.67 eV [93][94][95][155][156][157][158][159][160][161][162]. Our computed (2 + /0) using BB1k agrees well with the former DLTS signal and is a transition that we would expect to contribute significantly in the samples used experimentally.…”
Section: Znomentioning
confidence: 99%
“…Similar to SnO 2 , computational studies tend to indicate that the oxygen vacancy is deep, with the (2+/0) transition occurring at about 1 eV below the CBM [46][47][48][49][50][51][52][53]. There are a number of signals detected using deep level transient spectroscopy that have been attributed to oxygen vacancies [93][94][95], but the consistency of these attributions with results from computational studies is a matter of debate.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the charge state and its formation energy, the E3 level is unlikely related to the oxygen vacancy by itself. Recently, Chicot et al [20,21] suggested that the E3 level might be related to a dual vacancy V O − V Zn .…”
Section: Oxygen Vacancy (V O )mentioning
confidence: 99%
“…Just few years after D.V. Lang first described the basis of DLTS [68], several studies came out applying the technique to insulator-based devices [18][19][20][21][22][23]. The first report by Wang et al [147] used IGFETs to measure only interface traps, with a theoretical discussion on the procedure, which was further improved by Schulz et al [123], andÖzder et al [104,105] in Si MOS structures.…”
Section: Chapter 3 Deep Level Spectroscopy In Metal-insulator-semicomentioning
confidence: 99%
See 1 more Smart Citation